2020
DOI: 10.1080/02626667.2020.1711911
|View full text |Cite
|
Sign up to set email alerts
|

Drought impacts on water quality and potential implications for agricultural production in the Maipo River Basin, Central Chile

Abstract: Droughts can have serious negative impacts on the water quality needed for irrigated agriculture. The Metropolitan region of Chile is a relevant producer of high-value crops and is prone to droughts. Standardized Drought Indices were used to characterize meteorological and hydrological droughts for the period from 1985 to 2015. To understand the relationship between droughts and water quality, we evaluated the correlations between daily discharge and surface water quality observations. The threshold level meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(23 citation statements)
references
References 72 publications
1
20
0
2
Order By: Relevance
“…While the impact of drought was out of this project's scope, this declaration brings forth the ubiquitous challenges posed by climate change. Drought may decrease the water quality at the source [43,44]; in this vein, further research is needed to study the adaptiveness or resilience of the relationships we found against this effect.…”
Section: Discussionmentioning
confidence: 95%
“…While the impact of drought was out of this project's scope, this declaration brings forth the ubiquitous challenges posed by climate change. Drought may decrease the water quality at the source [43,44]; in this vein, further research is needed to study the adaptiveness or resilience of the relationships we found against this effect.…”
Section: Discussionmentioning
confidence: 95%
“…Para muitos animais essa faixa é ideal, por exemplo, para a maioria das espécies de peixes o pH deve se situar numa faixa de 6,5 a 8,5, já que fora desta há um comprometimento no seu grau de atividade e no apetite. Os resultados de pH observados estão de acordo com Guerrero et al (2020), que identificaram valores de pH mais altos em períodos de secas. Ainda segundo os autores, em anos secos, todo o ciclo da água é afetado pela redução da recarga dos reservatórios.…”
Section: Resultsunclassified
“…For the near future, climate change, also, will play an important role in the hydrological components, causing an increase of evapotranspiration and a decrease of precipitation, percolation, surface flow, and groundwater recharge [49]. Therefore, climate change impacts agricultural production, influencing the quality and quantity of water available for irrigation [50].…”
Section: The Context Of Climate In Chilementioning
confidence: 99%